Toxic Elements Leachability Tests on Autoclaved Flyash-Lime Bricks - Tanriverdi, Mehmet (Asian Journal of Chemistry, 2010)
In this study, a series of batch leach tests was carried out to investigate the leachability of some toxic elements contained in steam autoclaved flyash-lime bricks. The prime aim of these tests was to find out whether the lime based fly ash bricks are environmentally sound. The tests simulated the natural rain water and acid rain environment to understand the behaviour of the elements during weathering. Autoclaved fly ash-lime bricks have been tested using the methods of TCLP and ASTM Method A extraction to determine their toxicity levels.